Home » Blog » Use the method of undetermined coefficients to solve (1-x2)y′′ – 2xy′ + 6y = 0

Use the method of undetermined coefficients to solve (1-x2)y′′ – 2xy′ + 6y = 0

Consider the differential equation

    \[ (1-x^2)y'' - 2xy' + 6y = 0. \]

The solution to this differential equation has a power-series expansion

    \[ f(x) = \sum_{n=0}^{\infty} a_n x^n \qquad \text{with} \qquad f(0) = 1, \quad f'(0) = 0. \]

Using the method of undetermined coefficients obtain a recursion formula relating the terms a_{n+2} to the terms a_n. Give an explicit formula for a_n for each n and find the sum of the series.


First, we differentiate twice,

    \begin{align*}  f(x) &= \sum_{n=0}^{\infty} a_n x^n \\  f'(x) &= \sum_{n=1}^{\infty} na_n x^{n-1} \\  f''(x) &= \sum_{n=2}^{\infty} n(n-1)a_n x^{n-2}. \end{align*}

From the initial conditions f(0) = 1 and f'(0) = 0 we have

    \begin{align*}  f(0) &= \sum_{n=0}^{\infty} a_n x^n = a_0 = 1 \\  f'(0) &= \sum_{n=1}^{\infty} na_n x^{n-1} = a_1 = 0. \end{align*}

Now, we plug the expressions for y, \ y', and y'' back into the given differential equation,

    \begin{align*}  && (1-x^2)y'' - 2xy' + 6y &= 0 \\[9pt]  \implies && (1-x)^2 \left(\sum_{n=2}^{\infty} n(n-1)a_n x^{n-2} \right) - 2x \sum_{n=1}^{\infty} na_n x^{n-1} + 6 \sum_{n=0}^{\infty} a_n x^n &= 0 \\[9pt]  \implies && \sum_{n=2}^{\infty} n(n-1) a_n x^{n-2} - \sum_{n=2}^{\infty} n(n-1)a_n x^n - 2 \sum_{n=1}^{\infty} na_n x^n + 6 \sum_{n=0}^{\infty} a_n x^n &= 0 \\[9pt]  \implies && \sum_{n=0}^{\infty} (n+2)(n+1) a_{n+2} x^n - \sum_{n=2}^{\infty} n(n-1)a_n x^n - 2 \sum_{n=1}^{\infty} na_n x^n + 6 \sum_{n=0}^{\infty} a_n x^n &= 0 \\[9pt]  \implies && \left(\sum_{n=2}^{\infty} \left( (n+2)(n+1)a_{n+2} - n(n-1)a_n - 2na_n + 6a_n \right)x^n\right) + 2a_2 + 6a_3 x -2a_1 x + 6a_0 + 6a_1 x &= 0. \end{align*}

Then, we use the fact from above that a_0 = 1 and a_1 = 1 to get

    \begin{align*}  && \left( \sum_{n=2}^{\infty} \left( (n+2)(n+1)a_{n+2} - n(n-1)a_n - 2na_n + 6a_n \right) \right) + 2a_2 + 6a_3 x + 6 &= 0 \\[9pt]  \implies && \left( \sum_{n=2}^{\infty} \left( (n+2)(n+1)a_{n+2} - a_n (n^2 + n - 6) \right) \right) + 6a_3 x + 2a_2 + 6 &= 0 \\  \implies && \left( \sum_{n=2}^{\infty} \left( (n+2)(n+1)a_{n+2} - (n+3)(n-2)a_n \right)\right) + 6a_3 x + 2a_2 + 6 &= 0. \end{align*}

Since this sum is equal to 0, we know that every coefficient of every power of x must be equal to 0. First, we solve for a_2 and a_3,

    \begin{align*}  2a_2 + 6 &= 0 & \implies && a_2 &= -3 \\  6a_3 &= 0 & \implies && a_3 &= 0. \end{align*}

Then, we establish the recursive relationship between a_n and a_{n+2},

    \begin{align*}  && (n+2)(n+1)a_{n+2} - (n+3)(n-2)a_n &= 0 \\  \implies && (n+2)(n+1) a_{n+2} &= (n+3)(n-2)a_n \\  \implies && a_{n+2} &= \frac{(n+3)(n-2)}{(n+2)(n+1)} a_n \end{align*}

for all n \geq 0. Then since a_3 = 0 we have a_{2n+1} = 0 for all n (since for every odd integer n the formula for a_{n+2} has is multiplied by a_n, but each of these will be 0). For the even terms we have for n=2,

    \[ a_4 = \frac{(n+3)(n-2)}{(n+2)(n+1)} a_2 = \frac{(5)(0)}{(4)(3)} (-3) = 0.\]

This means all of the remaining even terms will be 0 as well. So we have

    \[ a_0 = 1, \quad a_1 = 0, \quad a_2 = -3, \quad a_3 = a_4 = \cdots = 0. \]

Hence,

    \[ f(x) = 1 - 3x^2. \]

2 comments

  1. Leland says:

    Big mistake here… the remaining terms do not ALL turn to zero after a4. Every other term will be zero from that point on, given that the recursive relation is between m and m+2… this leaves m+1, m+3, etc… to be nonzero.

    • Anonymous says:

      I don´t know if I understood your point, but the terms become zero as a_1=0 so a_3,a_5,… are zero and a_4=0 so a_6,a_8,… become zero too.

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):